A Phenomenological Case Study of Preparedness for Public Interest Lawyers - Paula E. McBride (Adult Education Research Conference, 2014)
The literature focusing on reform in legal education has failed to define what “preparedness” for a public interest lawyer means. In order to examine what conditions make a public interest lawyer graduate practice-ready, we must investigate the phenomenon which constitutes preparedness for public interest law.